2015
DOI: 10.4254/wjh.v7.i9.1192
|View full text |Cite
|
Sign up to set email alerts
|

Composite prognostic models across the non-alcoholic fatty liver disease spectrum: Clinical application in developing countries

Abstract: Heterogeneity in clinical presentation, histological severity, prognosis and therapeutic outcomes charac teristic of nonalcoholic fatty liver disease (NAFLD) necessitates the development of scientifically sound classification schemes to assist clinicians in stratifying patients into meaningful prognostic subgroups. The need for replacement of invasive liver biopsies as the standard method whereby NAFLD is diagnosed, graded and staged with biomarkers of histological severity injury led to the development of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 196 publications
(201 reference statements)
1
8
1
2
Order By: Relevance
“…ROC analysis revealed that miR122 has the potential to distinguish NASH from SS, because it predicts hepatocellular ballooning or lobular inflammation with an AUROC of 0.76. Although this predictive value is not good enough for an ideal biomarker, the ability of miR122 to predict NASH is quite similar to that of other studies [52,53,54]. However, as these authors suggested, compared to single biomarkers, the stepwise combination of different biomarkers can further improve the accuracy of diagnosing NASH.…”
Section: Discussionsupporting
confidence: 70%
“…ROC analysis revealed that miR122 has the potential to distinguish NASH from SS, because it predicts hepatocellular ballooning or lobular inflammation with an AUROC of 0.76. Although this predictive value is not good enough for an ideal biomarker, the ability of miR122 to predict NASH is quite similar to that of other studies [52,53,54]. However, as these authors suggested, compared to single biomarkers, the stepwise combination of different biomarkers can further improve the accuracy of diagnosing NASH.…”
Section: Discussionsupporting
confidence: 70%
“…Using hemodynamic data acquired during the combined cardiac catheterization and liver biopsy procedures, Figures show no significant correlation between TFS and inferior vena caval pressure, pulmonary vascular resistance, or univentricular end‐diastolic pressure, respectively. We found no significant correlations between TFS or elastography measurements and APRi (AST to platelet ratio index) scores, individual ALT values, or AST/ALT ratios …”
Section: Resultscontrasting
confidence: 59%
“…We developed a noninvasive, composite index, comprised of hepatic ultrasound SWE measurements, MELD‐XI scores, and time post‐Fontan, which strongly correlated with TFS from liver biopsy. Noninvasive, composite indexes, some with highly complex best‐fit equations employing several mathematical transformations, have been previously developed for noninvasively predicting non‐Fontan related liver fibrosis, after recognizing that individual markers had poor discriminatory power and limited clinical use in stratifying patients into prognostic subgroups …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations